1981
DOI: 10.1037/0097-7403.7.1.18
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine and time estimation.

Abstract: Three experiments were conducted to determine the effect of methamphetamine on the performance of rats in two timing tasks. When food sometimes followed the first response after T sec of a signal, the response rate increased to a peak near T sec and then declined. Methamphetamine decreased the time of the peak (Experiments 1 and 2). When one response (called a "short response") was reinforced following a short signal and a different response (a "long response") was reinforced following a long signal (where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

24
269
8

Year Published

1982
1982
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 281 publications
(301 citation statements)
references
References 20 publications
24
269
8
Order By: Relevance
“…Again, even without rapid learning of a new temporal discrimination, the experiment would show only that time was irrelevant if subjective time accurately reflected objective time. Maricq, Roberts, and Church (1981) found that methamphetamine decreased the point of indifference in a temporal estimation procedure in a manner consistent with about a 10010 increase in clock rate; Maricq and Church (in press) replicated this result and found that haloperidol increased the point of indifference in a manner consistent with a decrease in clock rate. In Laties's experiment, if haloperidol decreased the speed of the clock in the same proportion as it did the response rate, and the animal maintained a constant subjective time criterion, the number of responses before a switch to the left lever response would not change.…”
mentioning
confidence: 86%
“…Again, even without rapid learning of a new temporal discrimination, the experiment would show only that time was irrelevant if subjective time accurately reflected objective time. Maricq, Roberts, and Church (1981) found that methamphetamine decreased the point of indifference in a temporal estimation procedure in a manner consistent with about a 10010 increase in clock rate; Maricq and Church (in press) replicated this result and found that haloperidol increased the point of indifference in a manner consistent with a decrease in clock rate. In Laties's experiment, if haloperidol decreased the speed of the clock in the same proportion as it did the response rate, and the animal maintained a constant subjective time criterion, the number of responses before a switch to the left lever response would not change.…”
mentioning
confidence: 86%
“…An increase in arousal is most often associated with an increase in pacemaker speed, and this, in turn, increases the number of pulses accumulated within a given time period and produces an overestimation. However, this increase in pacemaker speed would produce a multiplicative effect, i.e., an increase in the magnitude of the time distortion as the length of stimulus durations increased (Maricq et al, 1981;Meck, 1983). In order to test this hypothesis, we compared the average d' of the shortest comparison durations (400, 600, and 800ms) with the average d' of the longest comparison durations (1200, 1400, and 1600ms), with an arousal account predicting an increase in d' for longer durations (Gil, Niedenthal, & Droit-Volet, 2007).…”
Section: Meditation Groupmentioning
confidence: 99%
“…Time estimation is based on the number of pulses accumulated, with more pulses leading to an increase in perceived duration. Arousal produces an overestimation of time due to an increase in the pacemaker's speed (Maricq, Roberts, & Church, 1981;Meck, 1983;Wearden & Penton-Voak, 1995; although see Lui, Penney, & Schirmer, 2011). In contrast, if attention to the task distracts from the processing of temporal information, this opens the switch and some pulses are lost.…”
Section: Introductionmentioning
confidence: 99%
“…The success of the IP model of interval timing is due in large part to the modularity of the clock, memory, and decision stages of the model which allows for ample theoretical and experimental evaluations and development at mathematical (Church et al, 1994;Gibbon and Church, 1981), behavioral (Church, , 1984Church and Deluty, 1977) and neurophysiological levels (Maricq and Church, 1983;Maricq et al, 1981;Olton et al, 1987;Olton et al, 1988), as well as for extensions to other fields such as counting (Meck and Church, 1983;Meck et al, 1985) and magnitude processing (Gallistel and Gelman, 1992).…”
Section: Introductionmentioning
confidence: 99%